A atuação d’A Rocha no Brasil: percepções sobre o cuidado ambiental no meio protestante brasileiro - Schimenes, Fernanda Ilinsky (2024)
This research investigates the work of the Christian environmental organization A Rocha Brasil from 2006 to 2020. The first chapter brings summaries of (1) the current situation of the climate emergency, (2) the relationship of Protestantism with the environment at a global level since its foundation, and (3) of a contemporary Protestant missiological line – that of the social gospel, which is related to the so-called theology of integral mission – in which care for creation is one of the priorities. Considering this context, the second chapter explores the history of A Rocha International from the embryonic project in the Algarve, Portugal, to the NGO's arrival in Brazil from a group of Protestant Christians inspired by the book by Peter Harris, founder of A Rocha. It addresses the differences in Brazil's performance compared to other national organizations of A Rocha around the world, the theological basis it defends, the projects it developed in the country with the churches (especially the Transformation Network – ReT), the difficulties it faced – funding, political polarization and issues in the team, for example – and the materials it produced such as books, videos, booklets and study guides. From this, perceptions about environmental care in the Brazilian Protestant milieu are outlined. Despite having closed its activities in 2020, Rocha Brasil left a significant legacy. The organization's impact in sensitizing the Protestant milieu to the environmental crisis is perceived on different fronts: in similar organizations such as the Renovar Nosso Mundo movement and in efforts to preserve the environment of areas, in the content produced by different Protestant denominations regarding environmental care, in seminars that include the theme in their curriculum etc